Correlation Between The Level Of Understanding Of HIV And The Lifestyle Of ODHA At Rsud Dr. T.C. Hillers Maumere In 2022 - Putera, Dewa Gede Agung Sasmara; Purnama, Asep (Universitas Nusa Cendana, 2023)
Human Immunodeficiency Virus (HIV) is a virus that attacks the immune system. If HIV is not treated, it can lead to AIDS (Acquired Immuno Deficiency Syndrome). The purpose of this study was to determine the relationship between understanding of HIV in people living with HIV and a healthy lifestyle in living life. This research is a descriptive study using a cross-sectional method. Data collection was carried out in February 2022 at the VCT Clinic of RSUD T.C. Hillers, Maumere, East Nusa Tenggara. Samples were taken by total sampling. The researcher asked the subject's willingness voluntarily and gave informed consent to participate in the study. Questionnaires were given to assess the knowledge and lifestyle of the research subjects. The questionnaire consists of three parts with a total of 81 questions. During one month of February 2022, there were 40 HIV-positive research subjects at the VCT Clinic who were willing to become subjects of the study by filling out the questionnaire provided. The results of this study indicate that there is a strong relationship between understanding HIV and the lifestyle of ODHA. A positive value indicates a one-way relationship between the two variables, the higher the understanding of HIV, the better the pattern of life. From the t-count value is 3.287 with a significance value of 0.002 <0.05, which means that the understanding of HIV among ODHA has a real or significant effect on the lifestyle of ODHA.